Accelerated weathering and soil burial effects on colour, biodegradability and thermal properties of bamboo/kenaf/epoxy hybrid composites. (October 2019) - Chee, Siew Sand; Jawaid, Mohammad; Sultan, M.T.H.; Alothman, Othman Y.; Abdullah, Luqman Chuah
Abstract: This study aims to gain insight into the influence of environmental effects on the colour, biodegradability, oxidation stability, thermal stability and complex modulus of bamboo/kenaf fiber reinforced epoxy hybrid composites. The composites were prepared by the hand lay-up technique, with a fixed loading of 40% fibers for all the composites. Three types of hybrid composites were prepared with different mixing ratios of bamboo fibers (B) to kenaf fibers (K): (i) 30:70, (ii) 50:50, and (iii) 70:30. Kenaf/epoxy and bamboo/epoxy composites, as well as pure epoxy, were also prepared for comparison purposes. The kenaf, bamboo and hybrid composites were exposed to UV radiation at elevated temperature and humidity, for a total exposure period of 156 h. The colour changes occurring during the weathering process were assessed by colorimetric analysis. The effects of soil burial on the developed composites were also studied for different time periods of 3, 6 and 12 months. Thermal properties, in terms of oxidation stability, thermal stability and dynamic mechanical properties, were determined by differential scanning calorimetry, thermogravimetric analysis and dynamic mechanical analysis, respectively. The results obtained from colorimetric analysis indicated that increasing the bamboo fiber loading in the formulation of hybrid composites induced higher total colour changes. The biodegradability of hybrid composites at higher kenaf loading increased as the soil burial period was longer. Overall, soil burial has led to more pronounced degradation, as compared to accelerated weathering, in terms of oxidation stability, thermal stability and dynamic mechanical properties. The findings of this work reveal that the hybrid composite formulation B:K:50:50 presents a balance of resistance to environmental effects, while maintaining the biodegradability characteristic, which makes it suitable for its use as a potential biocomposite material for structural applications. Highlights: Bamboo/kenaf/epoxy hybrid composites was fabricated by hand lay-up. Effects of accelerated weathering and soil burial was evaluated. Colour changes and biodegradability after environmental effects were evaluated. Thermal, oxidation stability and dynamic properties of hybrid composites were characterized. B:K:50:50 presents balance between resistance to environmental effects and biodegradability.